Magnetomechanical coupling in transducers - Zbigniew KACZKOWSKI (Archives of Acoustics)
The basic definitions of the coefficient of magnetomechanical coupling, k, based on generalized definitions of magnetic, mechanical (elastic) and piezo-magnetic energies, and on the magnetic quantities in the case of transmitting transducers and the mechanical quantities in the case of receiving transducers, i.e. for the mechanomagnetic coefficient, are presented. The relations between the coupling coefficient and the coefficients occurring in each system of piezo-magnetic equations and for different systems of equations and systems of units, and also for induction and magnetization, are derived.